2019
DOI: 10.1016/j.euf.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Age at First Presentation for Erectile Dysfunction: Analysis of Changes over a 12-yr Period

Abstract: Patients presenting for erectile dysfunction (ED) are younger than they were 10 yr ago. These findings may suggest an increase in ED awareness. Likewise, this age reduction could represent a worrisome increase in terms of ED incidence in young men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…In the present study in a nonclinical sample of Portuguese men younger than 40, there were 17.1% reporting symptoms of ED, mild in all but two cases. This figure is congruent with other studies indicating that ED in younger men is common (Capogrosso et al 2013(Capogrosso et al , 2016Capogrosso et al 2019;Dattatrya et al 2015;Nguyen et al 2017;Myakonatis et al 2018;Pozzi et al 2018;Rastrelli and Maggi 2017;Reed-Maldonado and Lue 2016;Yao et al 2018).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study in a nonclinical sample of Portuguese men younger than 40, there were 17.1% reporting symptoms of ED, mild in all but two cases. This figure is congruent with other studies indicating that ED in younger men is common (Capogrosso et al 2013(Capogrosso et al , 2016Capogrosso et al 2019;Dattatrya et al 2015;Nguyen et al 2017;Myakonatis et al 2018;Pozzi et al 2018;Rastrelli and Maggi 2017;Reed-Maldonado and Lue 2016;Yao et al 2018).…”
Section: Discussionsupporting
confidence: 92%
“…These feelings can amplify a sense of anxiety and depression, as well as decline levels of sexual satisfaction (Albaugh et al, 2017). Also, in another study, it has been found that good erectile function is associated with better good mood in men's lives (Capogrosso et al, 2019). In the study which evaluating 335 sexually active women, similarly, it was shown that sexual function in women is significantly associated with depression (Mezones-Holguin et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…However, likely, the findings of systemic diseases in young patients have not yet begun; although the relationship between ED and metabolic syndrome was shown in old males, this relationship was not demonstrated in males under 50 years (Heidler et al, ). It has been suggested that lifestyle changes such as smoking and alcohol use may play a role in increasing the incidence of ED in young men (Capogrosso et al, ). However, in our logistic regression analysis, the ability of these two factors to predict low IIEF‐EF domain score was not significant consistent with the findings of Pozzi et al ().…”
Section: Discussionmentioning
confidence: 99%
“…As a result, ED has been studied in detail in the elderly population and ED in young men has not been emphasised (prevalence, risk factors, treatment response, etc.). However, in some studies conducted recently, it was reported that the ED incidence has increased in men under the age of 40 and that men in this age group have been underdiagnosed due to less frequent referrals to clinicians (Capogrosso et al, ; Rastrelli & Maggi, ; Shamloul & Ghanem, ). It was demonstrated in a cross‐sectional, real‐time study that approximately one‐fourth of new ED cases have arisen in people younger than 40 years of age, and about half of them have serious ED (Capogrosso et al, ).…”
Section: Introductionmentioning
confidence: 99%